Citizens' views on prices of medicines reimbursed by the National Health Service: Findings from Italian online focus groups - Cinzia Colombo; Daniele Caldara; Rita Banzi (Wiley, 2024)
Abstract Introduction Access to medicines is one of the biggest challenges to health systems, affecting society and individuals. This study aims to explore citizens' opinions, perceptions and attitudes on the model of medicines' research and development (R&D) and price setting of medicines reimbursed by the Italian National Health Service. Materials and Methods We run four online focus groups, analysed through thematic analysis. Inclusion criteria: people aged 30-70 years, who had completed at least compulsory schooling (8-10 years), with no specialised knowledge about the subject. Exclusion criteria: healthcare workers, pharmaceutical and device industry employees, researchers and medicine policy board members. We aimed to include a purposive sample of 20 participants, variable in terms of age, educational level and place of residence. Results Eleven women and six men participated. The mean age was 53 years (range: 28-73). Most (n = 15) had a university degree or attended secondary schools. Eight had a job, five were not employed, and four were retired. In general, participants supported the role of the public health service. Almost all had limited knowledge of medicines' R&D and price setting. Most asked for transparency on medicine prices and negotiation criteria. Participants considered revenues of pharmaceutical companies disproportionate and most called for containment measures of profits. Most were in favour of a stronger public intervention in R&D and prices' negotiations. Few were sceptical of the public sector's ability to play this role. Discussion Medicines' prices were discussed as a health matter. Increasing citizens' awareness of these topics is needed by providing spaces and conditions to participate in the discussion, including different perspectives and interests. Patient or Public Contribution Members of BEUC-the European consumer organisation-proposed the project. Altroconsumo, an independent consumer organisation and OCU, a Spanish consumer organisation, participated in developing the project and the main topics to discuss. The Mario Negri Institute and Aplica cooperative-the Spanish methodological team-were involved by BEUC and their national organisations to define the methodology, organisational aspects and contents and conducted the focus groups.